FANSUBBING AS FEMINIST DISRUPTION IN CHINA - Wallis, Cara (AoIR Selected Papers of Internet Research, 2026)
This paper examines how young feminists dispersed across China engage in fansubbing, or translating and subtitling digital content, as a mode of feminist praxis. Feminist fansubbing shares similarities with other fansubbing practices in that its content can be entertaining and the act of fansubbing can create community among its practitioners. However, it also differs in that the motivation does not necessarily derive from actual fandom. Based on textual analysis and interviews, I show how it is driven by feelings and emotions and an ethical commitment to educate, encourage, and inspire others to become feminists. For this reason, I call it “femsubbing. Through drawing on Kathleen Stewart’s (2007) notion of ordinary affects and Michael Lambek’s (2010, 2015) ordinary ethics, I center how the women’s embodied passions and ethical judgments informed their fansubbing. They also sought to harness the power of networked communication and algorithmic recommendation systems to spread explicitly feminist messages as an ordinary ethical act. Strategies they used included changing the original video title, adding content in discussion and comments sections, and drawing connections between western, Korean, and Chinese feminism. However, they also faced challenges, including censorship, and challenges from within. Nonetheless, in an authoritarian context, femsubbing should be understood as a small but important means of disrupting often state-sanctioned sexism and misogyny.